TRAFFIC IMPACT ANALYSIS FOR THE DEVELOPMENT OF RSUD DR. SOESELO, TEGAL REGENCY - Fita Ayunina Lathifah; Ismiyati Ismiyati; Mudjiastuti Handajani (INFOKUM, 2022)
Hospital development dr. Soeselo Tegal Regency is a hospital effort to improve health services. The operation of the hospital building development will attract and stimulate movement. This issue will affect the smooth flow of traffic when the traffic load increases. Traffic impact analysis is an attempt to minimize the problem. This study aims to measure the traffic performance of dr. Soeselo Tegal Regency currently predicts traffic performance after it operates, calculates parking space requirements and provides several traffic scenarios. The analysis method uses PTV Vissim 22 traffic simulation software for road intersections and sections with Indonesian Road Capacity Manual 1997. The analysis results show that the traffic performance of existing conditions or without hospital development on roads and crossroads is still quite good, with the DS value below 0,75. While the results of the long-term analysis for the next five years with an increase in traffic load, there will be a decrease in traffic performance on the affected roads and intersections. So, to improve traffic performance by doing several traffic scenarios using Vissim software. The best scenario is to widen the road and regulate traffic circulation by implementing one-way streets during peak hours to increase traffic performance. The need and availability of parking space have met the demand for parking with the amount of land provided by Regional General Hospital dr. Soeselo.